Third phase of cardiac rehabilitation: a nurse-based â€œhome-controlâ€ model (Monaldi Archives for Chest Disease, 2015)
Background. Phase 3 is a critical point for cardiac rehabilitation: many problems donâ€™t allow achieving a correct secondary prevention, in particular regarding the relationship between patient and cardiologist. Aiming at ensuring continuity of care of phase 3 cardiac rehabilitation patients, we have developed a telemetric educational program to stimulate in them the will and capacity to become active co-managers of their disease. Methods. Nurses specialized in cardiac rehabilitation, with the collaboration of the general practitioners, contact the patients by scheduled phone calls to collect questionnaires about their health status and the result of biochemistry. All the results are analyzed by the nurses and discussed with each patient (educational reinforcement). The effects of this program of co-management of cardiac disease and secondary prevention are analyzed comparing each patient data at the discharge with data after one year and those coming from our archive (retrospective analysis). Results. The patients enrolled in this study pay much more attention to the amount of food they eat; they tend not to gain weight, and they restart smoking in a reduced proportion compared to patients not enrolled in the study. However, despite having received better information on their cardiac disease, their compliance to physical training, consumption of healthy food, and pharmacological therapy is not improved. Conclusions. This study focuses on the role of a continuous educational program of a cardiac rehabilitation unit after the patientâ€™s discharge. This home control program conducted by nurses specialized in cardiac rehabilitation, with the assistance of cardiologists, psychologists and physiotherapists, and in collaboration with the general practitioner, was quite cheap, and helped maximizing the knowledge of the disease and reinforcing correct life style in the patients. The results are not as good as expected, probably because one year does not represent a sufficient time, or because the educational intervention needs to be improved.
Keywords: adherence; telemedicine; secondary prevention